Evaluation of organizational and social commitments and related factors during the coronavirus pandemic of healthcare workers in northern Iran - Zahra Aghalari; Hans-Uwe Dahms; Somayeh Jafarian; Hemmat Gholinia (BMC, 2021)
Abstract Background Serious conditions caused by the coronavirus epidemic are expected to affect the mental and physical health, organizational and social commitments of healthcare workers. Therefore, this study aimed to evaluate the organizational and social commitments and related factors during the coronavirus pandemic of healthcare workers in northern Iran. Methods This descriptive-analytical study was conducted in 2020 among 260 healthcare workers of Babol health centers by a stratified-random sampling method. Data were collected according to a valid and reliable questionnaire consisting of three parts: 8 questions about personal and job characteristics, 15 questions from Porter Organizational Commitment Questionnaire (OCQ), 15 questions from Carroll's social responsibility. Each question was scored on the Likert scale of organizational and social commitment questionnaires. Data were analyzed by chi-square and logistic regression. P < 0.05 was considered as statistically significant. Results None of the healthcare workers belonged to the category of low organizational commitments. A portion of 27.7% of the healthcare workers had moderate organizational commitments and 72.3% had high organizational commitments. A portion of 9.2% of the healthcare workers had moderate social commitments and 90.8% had high social commitments. Chi-square showed that education (p = 0.001), job position (p = 0.001) and the area in which healthcare workers were present for service (p = 0.002) were significantly associated with organizational commitments. According to OR in the logistic regression model, healthcare workers with master's and doctoral education levels had 3.482 times more social commitments than others and the health group had 2.455 times more social commitments compared to the treatment group. Conclusion The results of this study showed that at the time of the coronavirus outbreak, the healthcare workers in Babol had very positive and high organizational and social commitments. As the world struggles with the coronavirus pandemic, employee and organizational productivity may decline due to the fear and anxiety of healthcare workers in various organizations. It is expected that managers of health-related organizations, social, economic, and cultural organizations use the results of this study to identify factors affecting the organizational and social commitments of employees and strengthen them.